2014
DOI: 10.1051/0004-6361/201424741
|View full text |Cite
|
Sign up to set email alerts
|

Inversion of stellar fundamental parameters from ESPaDOnS and Narval high-resolution spectra

Abstract: The general context of this study is the inversion of stellar fundamental parameters from high-resolution Echelle spectra. We aim at developing a fast and reliable tool for the post-processing of spectra produced by ESPaDOnS and Narval spectropolarimeters. Our inversion tool relies on principal component analysis. It allows reducing dimensionality and defining a specific metric for the search of nearest neighbours between an observed spectrum and a set of observed spectra taken from the Elodie stellar library.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…Because the candidate is exceptionally bright, and thus amenable to future characterization, we investigated the signal more closely than others, as explained below. The star has been characterized by many groups over the years (e.g., Valenti & Fischer 2005;Paletou et al 2015). It lies at a distance of 35.296±0.052pc (Gaia Collaboration et al 2018) and its parameters are T eff =6120±50 K, R * =1.15±0.04 R e , M * =1.26±0.19 M e (Valenti & Fischer 2005), in good agreement with our derived values from Gaia DR2 and isochrones.…”
supporting
confidence: 86%
“…Because the candidate is exceptionally bright, and thus amenable to future characterization, we investigated the signal more closely than others, as explained below. The star has been characterized by many groups over the years (e.g., Valenti & Fischer 2005;Paletou et al 2015). It lies at a distance of 35.296±0.052pc (Gaia Collaboration et al 2018) and its parameters are T eff =6120±50 K, R * =1.15±0.04 R e , M * =1.26±0.19 M e (Valenti & Fischer 2005), in good agreement with our derived values from Gaia DR2 and isochrones.…”
supporting
confidence: 86%
“…According to Kenyon & Hartmann (1995), this range of colors is centered on (R-I) c =0.75, i.e., the spectral type dK7. However, when we compiled and derived effective temperatures with the PCA-based inversion method (see Paletou et al 2015a and Section 3) for this sample of late-K dwarfs, we found on average higher temperatures than what would be expected from the (R-I) C -T eff tabulation of Kenyon & Hartmann (1995). We give the stellar parameters and spectral types of our late-K dwarf sample in Table 1.…”
Section: Selection Of a Sample Of Late-k Dwarfsmentioning
confidence: 84%
“…In the latter paper, stellar spectra of FGK stars were inverted using a so-called "learning database" made from the Elodie stellar spectra library (see Prugniel et al 2007): the "learning" occurs by using observed spectra for which fundamental parameters had already been evaluated. We note that the spectra considered in Paletou et al (2015a) had typical spectral resolutions  of 50,000 and 65,000: these are significantly lower than the resolution of the HARPS and SOPHIE data that will be analyzed in the present paper.…”
Section: Pca-based Inversion Of Stellar Fundamental Parameters For Lamentioning
confidence: 88%
See 2 more Smart Citations